Necrotizing enterocolitis: a potential protective role for intestinal alkaline phosphatase as lipopolysaccharide detoxifying enzyme - Martins, Raquel Dos Santos; Hulscher, Jan B. F.; Timmer, Albert; Kooi, Elisabeth M. W.; Poelstra, Klaas (Frontiers in Pediatrics, 2024)
Introduction Necrotizing enterocolitis (NEC) is a life-threatening inflammatory disease. Its onset might be triggered by Toll-Like Receptor 4 (TLR4) activation via bacterial lipopolysaccharide (LPS). We hypothesize that a deficiency of intestinal alkaline phosphatase (IAP), an enzyme secreted by enterocytes that dephosphorylates LPS, may contribute to NEC development. Methods In this prospective pilot study, we analyzed intestinal resection specimens from surgical NEC patients, and from patients undergoing Roux-Y reconstruction for hepatobiliary disease as controls. We assessed IAP activity via enzymatic stainings and assays and explored IAP and TLR4 co-localization through immunofluorescence. Results The study population consisted of five NEC patients (two Bell's stage IIb and three-stage IIIb, median (IQR) gestational age 25 (24–28) weeks, postmenstrual age at diagnosis 28 (26–31) weeks) and 11 controls (unknown age). There was significantly lower IAP staining in NEC resection specimens [49 (41–50) U/g of protein] compared to controls [115 (76–144), P = 0.03]. LPS-dephosphorylating activity was also lower in NEC patients [0.06 (0–0.1)] than in controls [0.3 (0.2–0.5), P = 0.003]. Furthermore, we observed colocalization of IAP and TLR4 in NEC resection specimens. Conclusion This study suggests a significantly lower IAP level in resection specimens of NEC patients compared to controls. This lower IAP activity suggests a potential role of IAP as a protective agent in the gut, which needs further confirmation in larger cohorts.